Numerical Simulation of Stainless Steel Powder Feeding in a Coaxial Nozzle for High Powder Efficiency in Laser Direct Energy Deposition - Kumar, Hemanth; M, Manjaiah (Frontiers in Mechanical Engineering, 2022)
Direct energy deposition (DED) is an efficient manufacturing process for the fabrication of complex parts and repair of worn-out turbine blades. In DED, all the injected powder is not going to melt and solidify due to spattering, reflection, ejection, effect of inert gas, and turbulence around the melt pool. In this study, through numerical simulation, the effect of powder size and inert gas flow under coaxial nozzle was analyzed. The number of particle participation in the melt pool by the effect of inert gas and the size of powder particles were analyzed. The powder particle sizes considered for the study were 50–60, 60–70, 70–80, 80–90, 90–100, and 45–90 µm. Argon and helium gases were used as carrier gas and shielding gas, respectively. According to gas–solid multiphase simulation, the convergence distance of the powder flow and powder participation focal point was analyzed through numerical simulation. The simulated results showed that using argon gas as a carrier gas produced high powder efficiency compared to helium gas. The focal point is forming at 11.86 mm, approximately 12 mm from the nozzle exit, which occurred for 60–70-µm particle size. The powder particle participation efficiency obtained was 64.1% using argon gas as carrier gas.